Cattle herd structure and dynamics at Abet - Milligan, K. (International Livestock Centre for Africa, 1978)
Presents results of a field data collection as to the age & sex wise herd structure of settled Fulani cattle herds at Abet in Nigeria. Includes a discussion on herd sizes, sex ratio at various ages & factors affecting it i.e. losses, sales/purchases, percentage of milking cows and calf: cow ratios, inferred from collected data.